Workplace writing in English: insights from Malaysian bank managers. - Nur Ehsan Mohd Said,; Saadiyah Darus, (Penerbit UKM, 2011)
This paper discusses the findings of a series of interviews with three local commercial bank managers, describing workplace writing among Malaysian bank executives as writers of English as a second language (ESL). Existing studies on workplace writing are found to be limited in number, particularly those that investigate writing among bank executives. In addition, the status of English as a second language (L2) poses an inherent linguistic challenge for Malaysians and, thus, results in a different set of writing needs than for native writers of English. These factors illustrate the need for an in-depth investigation of the Malaysian banking institutions context. This study is part of a larger research, and data from this study was collected through semi-structured interviews,involving three managers as experienced informants. Their feedback was divided into four categories: the language of correspondence, the writing responsibilities at each bank, the roles of computers and writing software to assist in writing tasks, and the future of writing software programs in Malaysia. The findings can be summarized as follows: 1) English was the correspondence language in two out of the three banks; 2) writing was a frequent responsibility among most of the executives; 3) the executives were generally not provided any assistance with regard to writing; and, 4) a writing software program tailored for ESL writers was deemed a necessary form of assistance in consideration of the multiple tasks that need to be performed by the bank executives.